Re-significando a ação clínica psicológica na assistência à criança queimada - Carvalheira, Ivana Magaly Lima Alencar (2003)
Considering the pain and suffering of the burned child who is in hospital, this author was concerned mostly with the kinds of current clinical help which are offered by the psychology professionals staff. From this view point when one researched about the saber fazer , that is, the psychological and clinical know-how, there were a great number of possibilities as to the fazer saber , e.g. how to reach the suffering child in his/her innerself and let him/her know that there is someone who in fact can help. It was found out that there were a number of attitudes, actions, interventation and interpretation which the psychologist could make use of in his relationship and care for the subject, the burned child. Therefore, the psychologist and/or researcher should be conscious about how broad the psychological clinical field is, and further he/she needs to understand clearly what may help as well as what may prevent a certain contextual action . One should start from understanding the subject s individual experience as a unique human being. This study aims to take a rather different look at the burned child specific experience, and tries to provide a new meaning to the psychological clinical action, inside a hospital, enlightened by both the existential phenomenon and attitudes for the psychological clinical action. The qualitative methodology was chosen, and it was inspired by the narrator himself. It was also supported by the phenomenal method for interpretation. The material analysed is made up of narratives based on the psychologist/researcher experiences, as well as from the burned child and the mother, who were in the Burned Treatment Center (BTC). In addition, reports from professionals belonging to the same health staff were considered. Finally , special attention was given to both the experienced/affectionate knowledge and the theoretical one, all deriving from talks to area field experts. It was discovered that the psychological action done at the BTC is in the pratical-theoretical field from the Psychological Advice, and it is deemed as an educational and psychological-clinical practice, in an interdisciplinary dimension of a clinical social action. M oreover, some special peculiarities were found from the communication among the professional psychologist, the burned child and the mother. Those peculiarities were the tools which facilitated the psychologist